2018
DOI: 10.1021/acs.jmedchem.8b00745
|View full text |Cite
|
Sign up to set email alerts
|

Succinimide-Based Conjugates Improve IsoDGR Cyclopeptide Affinity to αvβ3 without Promoting Integrin Allosteric Activation

Abstract: The isoDGR sequence is an integrin-binding motif that has been successfully employed as a tumor-vasculature-homing molecule or for the targeted delivery of drugs and diagnostic agents to tumors. In this context, we previously demonstrated that cyclopeptide 2, the product of the conjugation of c(CGisoDGRG) (1) to 4-( N-maleimidomethyl)cyclohexane-1-carboxamide, can be successfully used as a tumor-homing ligand for nanodrug delivery to neoplastic tissues. Here, combining NMR, computational, and biochemical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…This change was ascribed to the substitution of a Trp residue for a Ser immediately after the RGD sequence because the Trp forms a π-π interaction with β 3 Y122 on the β 1-α1 loop, thus preventing the latter's movement toward the MIDAS, a key element in triggering the conformational change (63). The importance of interacting with Y122 to prevent the conformational change in αVβ3 is also supported by studies demonstrating that nonenzymatic conversion of Asn to isoAsp in the GNGRG sequence in fibronectin repeat 5 results in the repeat developing high affinity for αVβ3; the cyclic peptide CisoDGRC retains this high affinity without inducing the conformational change in αVβ3 (64-66) because the C1 of the peptide interacts via its N-terminus with the Y122 carbonyl in β 3 (65,66).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This change was ascribed to the substitution of a Trp residue for a Ser immediately after the RGD sequence because the Trp forms a π-π interaction with β 3 Y122 on the β 1-α1 loop, thus preventing the latter's movement toward the MIDAS, a key element in triggering the conformational change (63). The importance of interacting with Y122 to prevent the conformational change in αVβ3 is also supported by studies demonstrating that nonenzymatic conversion of Asn to isoAsp in the GNGRG sequence in fibronectin repeat 5 results in the repeat developing high affinity for αVβ3; the cyclic peptide CisoDGRC retains this high affinity without inducing the conformational change in αVβ3 (64-66) because the C1 of the peptide interacts via its N-terminus with the Y122 carbonyl in β 3 (65,66).…”
Section: Introductionmentioning
confidence: 88%
“…62 The importance of interacting with Tyr122 to prevent the conformational change in αVβ3 is also supported by studies demonstrating that non-enzymatic conversion of Asn to isoAsp in the GNGRG sequence in fibronectin repeat 5 results in the repeat developing high affinity for αVβ3; the cyclic peptide CisoDGRC is reported to retain this high affinity without apparently inducing the conformational change in αVβ3 63,64 because the C1 of the peptide interacts via its N-terminus with the Tyr122 carbonyl in β3. 63,64 Based on Arnaout's observations, we synthetically modified the high-affinity RGD-based αVβ3 antagonist MK-429 so as to establish a π-π interaction with β3 Tyr122, guided by a threedimensional molecular model of MK-429's interaction with αVβ3 refined by molecular dynamics (MD) simulations. We searched for compounds that inhibit the adhesion of HEK-293 cells expressing αVβ3 to one of its ligands (fibrinogen), but do not trigger the activating conformational change in the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cytometry analysis of α v β 3 integrin was carried out as described previously . Briefly, human melanoma MSR3 cells were detached, washed, and re‐suspended with Dulbecco's phosphate‐buffered saline (DPBS with Ca 2+ and Mg 2+ ) containing 1 % FCS (binding buffer) in the presence of an RGD‐ or isoDGR‐containing compound (0, 50, or 500 μ m ) and one of the following antibodies, LM609 (10 μg mL −1 ) or AP5 (10 μg mL −1 ), for 90 min in ice (3×10 5 cells/100 μL in binding buffer).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that peptides containing isoAsp-Gly-Arg (isoDGR), a tripeptide motif that recognizes the αvβ3 integrin overexpressed in tumor vessels and on different tumor cell types (Avraamides et al, 2008;Desgrosellier and Cheresh, 2010), can be exploited as ligands for targeted delivery of various compounds to tumors, including drugs, imaging compounds and nanoparticles (Curnis et al, 2008;Curnis et al, 2013;Corti et al, 2017;Nardelli et al, 2018). In particular, we have shown that a cyclic CGisoDGRG peptide (called iso1) coupled to human serum albumin (iso1-HSA) can be used for the functionalization of nanogold bearing TNF or interleukin-12 (IL12), to enable "active" targeted delivery of nanoparticles to the tumor vasculature (Curnis et al, 2013;Gasparri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%